COMMUNITY EMPOWERMENT STRATEGY TEMAN PROGRAM BASED - Ria Adriyani; Agus Siswanto; Rachmat Indrianto (DIA: Jurnal Administrasi Publik, 2021)
People on the north coast of Cirebon Regency depend on their livelihood from catching sea products. If the weather is terrible, they cannot go to sea, so they do not get income. The community's inability to have a substantial income is the aim of this study, namely how to create productive business groups for fishermen's wives. They help people who can run small-scale businesses to get assistance from academics, industry, and government with the term Triple Helix. The strategy to build the synergy of these three elements is applied through the TEMAN program (Economic Order of the Fishermen's Community) in collaboration between community service in tertiary institutions in partnership with industry in villages around industrial areas through community empowerment efforts, thus forming business groups that produce products in the form of crackers that utilize the remaining processed fish and fat/small crab lemi become a fish paste and crab crackers. The method approach used is descriptive qualitative because it is related to social problems in the community, how to build motivation in the fishermen's wife group to do business so that they can earn even though they are small but sustainable or generic income. The findings from the research on community empowerment strategies based on the TEMAN Program show that access to natural resources, access to community participation, access to markets, and access to information and knowledge proves that community empowerment programs can make small business groups become independent and help economic sustainability. Families of fishermen on the coast.